FIRST EPISODE PSYCHOSIS: CLINICAL CHARACTERISTICS AND SUBSTANCE ABUSE STYLE IN PATIENTS AT THE ACUTE CARE UNIT - Palma Sevillano, Carolina; Cañete Crespillo, José; Farriols Hernando, Nuria; Soler Llobet, Fátima; Julià Zapata, Jordi (Anales de Psicología / Annals of Psychology, 2005)
Aim: To study the clinical, sociodemographic characteristics and substance abuse style in the first episode of psychosis. Method: Included, were all the first episode cases of psychosis from January 2000 to September 2003. The final sample was formed by 82 patients that were admitted into the acute psychiatric unit of Mataro’s Hospital. Outcomes: Of the total sample, 56% of patients presented abuse of toxic substances in recent years of which 23.2% declared an increase of consumption during the 3 weeks prior to admission. We observed a significant correlation among those patients and the duration of their admittance (p=.043, r Pearson). Also among the drugs consumption history there was an earlier beginning of psychotic disorder (p=.02). Conclusions: The substance abuse in people who have a psychotic disorder, leads us directly to the eternal reflection that if the correlation found between both variables would be able to be more than just a mere association and that the consumption would be a predictive factor to the beginning or transition to first episode-psychosis.